Investigation of the performance of cement mortar incorporating lithium slag as a super-fine aggregate - Dong, Shuangkuai; Tu, Shengwen; Chen, Liangliang; Wu, Fufei; Xie, Lilan; Zhuo, Qi; Yu, Songhan (Frontiers in Materials, 2023)
As a by-product of lithium salt, the emission of lithium slag keeps constantly increasing every year due to the increased demand for lithium salt. Therefore, the utilization of lithium slag faces a huge challenge. In this study, a new approach to using lithium slag as super-fine aggregate in cement system was proposed. The results indicated that lithium slag as super-fine aggregate replaces 0%, 30%, 50%, 70%, and 100% standard sand, The main hydration products of cement lithium slag paste were calcium silicate hydrate gel, calcium hydroxide, unhydrated particles and a little of ettringite. Lithium slag as super-fine aggregate could reduce significantly dead load of structure, significantly enhance flexural strength and compressive strength and significantly enhance the peak stress of mortar, and no more than 50% lithium slag could significantly enhance the permeability of mortar. Based on the above experimental study, the replacement rate of lithium slag as super-fine aggregate could reach 50%, at this time, the amount of lithium slag as super-fine aggregate was about five times that of lithium slag as supplementary cementitious material. Therefore, the study brings an innovation about the utilization of lithium slag in cement system and improves performance of cement mortar.